Micro Electromechanical System Navigation Assists Femoral Extramedullary Alignment Osteotomy in Total Knee Arthroplasty: A Single‐Blind Randomizing Study - Mingjiang He; Hongmei Zhang; Peiyan Hu; Lin Jing; Pengcheng Shan (Orthopaedic Surgery, 2023)
Objective A micro‐electromechanical system (MEMS) was developed based on spatial alignment and navigation technology to assist femoral extramedullary alignment osteotomy (FEAO) in total knee arthroplasty (TKA). The system can locate and adjust the femoral distal condylar osteotomy (FDCO) to obtain a better femoral prosthesis placement. It is a portable navigation device and provides an innovative approach for FDCO. Methods Sixty patients who suffered from severe knee osteoarthritis who underwent unilateral TKA from May 14, 2021 to May 30, 2022 were randomly divided into a MEMS‐FEAO group and a conventional femoral intramedullary alignment osteotomy (FIAO) group, with 30 cases in each group for a controlled retrospective study. The hip‐knee‐ankle angle (HKAA) of the lower limb was measured before and after surgery, the femoral valgus angle (FVA) was measured preoperatively, and the femoral prosthesis valgus angle (FPVA) and the femoral prosthesis flexion angle (FPFA) were measured postoperatively following computed tomography imaging protocols. Measurement data is statistically described as mean ± standard deviation c. The count data is described by frequency (constituent ratio) using the rank sum test. Result A total of 6.7% (2/30) of FEAO compared to 20.0% (6/30) of FIAO cases were postoperative deviations where the HKAA exceeded ±3° of neutral alignment (p < 0.05). The postoperative HKAA was 178.74° ± 1.56° versus 176.64° ± 3.39° (p < 0.05), the HKAA deviation was 1.25° ± 1.56° versus 3.36° ± 3.40° (p < 0.05), and the FPFA was 4.85° ± 2.46° versus 6.60° ± 1.86°(p < 0.05). Therefore, the differences were all statistically significant between the two groups. However, the FPVA was −0.59° ± 2.73° versus −0.80° ± 2.85° (p > 0.05), and there was no statistical significance between the two groups. Conclusion The MEMS‐FEAO system can improve the accurate alignment and can be utilized as a locator to obtain the best femoral prosthesis placement in TKA and significantly reduce the rate of poor force line of the lower limb.